2006
DOI: 10.1073/pnas.0602678103
|View full text |Cite
|
Sign up to set email alerts
|

Transaldolase is essential for maintenance of the mitochondrial transmembrane potential and fertility of spermatozoa

Abstract: Fertility of spermatozoa depends on maintenance of the mitochondrial transmembrane potential (⌬ m), which is generated by the electron-transport chain and regulated by an oxidation-reduction equilibrium of reactive oxygen intermediates, pyridine nucleotides, and glutathione (GSH). Here, we report that male mice lacking transaldolase (TAL) ؊/؊ are sterile because of defective forward motility. TAL ؊/؊ spermatozoa show loss of ⌬m and mitochondrial membrane integrity because of diminished NADPH, NADH, and GSH. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 45 publications
1
76
1
Order By: Relevance
“…ALR/Erv1 catalyzes oxidative protein folding with the generation of disulfides and the reduction of oxygen to hydrogen peroxide, indicating its direct contribution to the oxidative stress. It has been reported that the human spermatozoon is highly susceptible to oxidative stress and disulfide bond formation is a very important issue in sperm physiology leading to a finely regulated redox status, which is needed to stabilize sperm nucleus and tail [33,34]. In addition, ALR performed the export of iron/sulfur (Fe/S) clusters from the mitochondrial matrix, contributing to the biogenesis of cytosolic Fe/S proteins and to cellular iron homeostasis [10].…”
Section: Discussionmentioning
confidence: 99%
“…ALR/Erv1 catalyzes oxidative protein folding with the generation of disulfides and the reduction of oxygen to hydrogen peroxide, indicating its direct contribution to the oxidative stress. It has been reported that the human spermatozoon is highly susceptible to oxidative stress and disulfide bond formation is a very important issue in sperm physiology leading to a finely regulated redox status, which is needed to stabilize sperm nucleus and tail [33,34]. In addition, ALR performed the export of iron/sulfur (Fe/S) clusters from the mitochondrial matrix, contributing to the biogenesis of cytosolic Fe/S proteins and to cellular iron homeostasis [10].…”
Section: Discussionmentioning
confidence: 99%
“…The collapse of Δψ m as a response to pathological states, such as anoxia or as a response to disordered mitochondrial respiration, will limit mitochondrial Ca 2+ uptake and may contribute to cellular pathophysiology [32,34]. Mitochondrial Ca 2+ import is an electrogenic process, as the movement of Ca 2+ is not countered by any other ion exchange and therefore acts like an inward current, tending to depolarize the mitochondrial membrane through increasing the permeability of the voltage-dependent anion channel (VDAC) [35].…”
Section: Mitochondrial Ca 2+ and Mitochondrial Transmembrane Potentialmentioning
confidence: 99%
“…Unlike G6PD and TK deficient mice which are not viable (25,26), heterozygous (TALþ/7) or homozygous (TAL7/7) TAL-deficient mice developed normally with the exception of sperm dysmotility and infertility due to the loss of Dc m (27). TAL7/7 spermatozoa show loss of Dc m and mitochondrial membrane integrity due to diminished NADPH, NADH, and glutathione.…”
Section: Tal Deficiency In Micementioning
confidence: 99%
“…Complete TAL deficiency also resulted in marked accumulation of S7P in the testis of TAL7/7 mice (27). S7P is a substrate of the forward reaction of TAL that generates G6P for NADPH production by enzymes of the oxidative phase of the PPP (Fig.…”
Section: Metabolic Consequences Of Tal Deficiency Are Cell Type-specificmentioning
confidence: 99%
See 1 more Smart Citation